Exploring paediatric burns : narrative accounts from caregivers in Khayelitsha, Cape Town - Yako, Jon Piko Wycliffe (Department of Psychology, 2014)
Studies conducted in the area of burns have recently begun to document the psychological implications of the condition. Burn survivors are often reported to suffer from post-traumatic stress disorder, depression, and social withdrawal. Difficulties in the self-concept domain have also been reported. No study in the country has captured the incidence of burns and its consequences, from the caregivers' perspective. It is this group of people that have been identified as playing a vital role in the child's recovery and adjustment. It is this same group that is also considered to be at high risk for experiencing ""caregiver burden"" linked with caring for the ill child.